2017
DOI: 10.1177/1474704917735937
|View full text |Cite
|
Sign up to set email alerts
|

Contrafreeloading in Rats Is Adaptive and Flexible: Support for an Animal Model of Compulsive Checking

Abstract: Contrafreeloading involves working unnecessarily to obtain a reward that is otherwise freely available. It has been observed in numerous species and can be adaptive when it provides an organism with updated information about available resources. Humans frequently update their knowledge of the environment through checking behaviors. Compulsive checking occurs when such actions are performed with excessive frequency. In a putative animal model of compulsive checking, rats treated chronically with the dopamine ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For instance, environmental cues that signal reward availability increase attempts to seek out (Estes, 1948; Corbit and Balleine, 2016) and retrieve reward (Marshall and Ostlund, 2018). While the ability to develop and modify action sequences is normally adaptive, this process may become dysregulated in certain conditions, such as obsessive-compulsive disorder (Joel and Avisar, 2001; Korff and Harvey, 2006; Frederick and Cocuzzo, 2017) and drug addiction (Tiffany, 1990; Graybiel, 2008; Volkow et al, 2013), leading to maladaptive behaviors. Despite this, the behavioral and neural mechanisms responsible for regulating reward seeking and retrieval are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, environmental cues that signal reward availability increase attempts to seek out (Estes, 1948; Corbit and Balleine, 2016) and retrieve reward (Marshall and Ostlund, 2018). While the ability to develop and modify action sequences is normally adaptive, this process may become dysregulated in certain conditions, such as obsessive-compulsive disorder (Joel and Avisar, 2001; Korff and Harvey, 2006; Frederick and Cocuzzo, 2017) and drug addiction (Tiffany, 1990; Graybiel, 2008; Volkow et al, 2013), leading to maladaptive behaviors. Despite this, the behavioral and neural mechanisms responsible for regulating reward seeking and retrieval are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings correlate with studies suggesting that information is most valuable when variance is greatest (Bell, 1991). Interestingly, contrafreeloading in rats is affected by administering drugs that influence the dopamine system to favor information-gathering (Frederick & Cocuzzo, 2017), also suggesting the rewarding nature of such behavior. Again, these data do not entirely explain the existence of contrafreeloading in other contexts.…”
mentioning
confidence: 99%
“…Moreover, a study on macaques (Macaca fuscata) observed contrafreeloading-like behavior when the playing of a movie on a cage-adjacent screen was substituted for food as the rewarding outcome [92]. Another study on rats (Rattus norvegicus) indicated that contrafreeloading engages the dopamine system of the brain, meaning that the behaviors result in a neurological "rush" that is similar to the thrill of a hunt [93]. This helps to explain why enrichment strategies targeting hunting-oriented behaviors are quite successful in big cats, as they alleviate the boredom caused by the inability to hunt [94][95][96].…”
Section: Effective Environmental Enrichment Approachesmentioning
confidence: 99%